DAMPAK KEBERADAAN INDOMARET TERHADAP KONDISI SOSIAL EKONOMI PEDAGANG PASAR TRADISIONAL DI KELURAHAN TERJUN KECAMATAN MEDAN MARELAN - OK LAKSEMANA LUFTI (Welfare StatE, 2013)
The research aims to find out how much of an impact since the existence  Indomaret outlets in the city field, particularly in sub-urban terrain Marelan plunge towards the existing wholesalers around the traditional market. In fact the existence of traditional markets is uneven and there were so many, and is very close to the traditional market in particular wholesaler. Giving rise to concerns of the wholesalers themselves. Place researchers doing research there are some problems related to competition, seemed to have stood 4 Indomaret outlets were located very close to the wholesaler or Indomaret itself. The condition causes many consumers are turning to shopping digerai Indomaret, but before the establishment of the booth, consumers do their shopping at a wholesaler. The techniques with descriptive methods - that is, with reference to qualitative research strategies, such as in-depth interviews (deep interview) and reporting and collection of data through observation of their activities observed. Descriptive Methodology - Qualitative allow researchers to analyze the effects produced by the presence of Indomaret outlets to wholesalers, as well as permission to build a store in the city Indomaret field. This study lead to the conclusion that there are many impacts of development Indomaret outlets around the traditional market and around the wholesaler. The existence of modern aka mini branded stores Indomaret in northern Sumatra, especially field, is no longer a new story. Residents have started to get used to shopping on network franchises. Unfortunately, as it was a small trader from marginalized sampa some even folded. Impression traditional markets are hot, chaotic, dirty, muddy, unsafe because many pickpockets are very contradictory dengam store modern air conditioning market, comfortable, service, independently and quickly and relatively safe from pickpockets. This condition is a serious threat to the survival of small businesses and medium-sized traders. The presence of shopping centers like malls and shopping centers in its class has now mushroomed in Indonesia and has changed the mindset of Indonesian people to shop in Indonesia.   Keywords: wholesaler, Indomaret outlets, traditional markets, socio-economics